Interpretation of the Subsurface Structure of Batanta Island Using Gravity Method and 2D Modeling - Ceni Febi Kurnia Sari; Fajar K. Rohmala; Charly Bravo Wanggai; Zulfikar Mardiyadi; Eka Febi Selvandy Putri (Universitas Negeri Padang, 2026)
Batanta Island in Raja Ampat, West Papua, is located in an active tectonic zone dominated by fault structures and igneous rock intrusions, thus possessing significant geological potential. This research aims to identify the subsurface structure of the island using the gravity method that has undergone drift, tidal, topographic, and Bouguer corrections, followed by regional-residual component separation. 2D modeling with GM-SYS software was used to construct geological cross-sections based on rock density distribution. Results show the presence of several main units, including massive lava, breccia, Quaternary deposits, and high-density intrusion bodies (±3.00 g/cm³) that are interpreted as diorite. An active fault zone and lithological boundary were also found, which serve as the main controllers of geological structure. These findings indicate the presence of mineralization potential and complex geological dynamics, and serve as an important initial contribution to further geological exploration on Batanta Island and its surroundings